Domestic Violence; An Unexpected Crisis in the Corona Virus Period: Implications for Ugandan Households - Luwemba, Musa Maswanku (Islamic University Journal of Social Sciences, 2022)
The year 2020 has seen a major pandemic known as Corvid 19(Corona Virus 2019) which has required governments to devise interventions to manage this new ‘pandemic’. To this, Ugandan households as it has happened elsewhere have been forced to ‘stay at home’ so as to avoid free interaction which to health officials is a basis for the pandemic. This has not been free of costs. An evident cost is increased cases of domestic violence. It is only ‘essential services’ that have been allowed to move and work (say health officials, selected public service), legal, to mention but a few. The masses are forced to stay at home with their people which is good but also bad for people who are not used to staying at all for so long a time. The question is what this implies for third world societies like Uganda and how prepared such households are for this prevalent domestic violence. Violence against women tends to have increased in any emergency, including epidemics. Stress, disruption of social and protective networks, increased economic hardship and decreased access to services can exacerbate the risk of women suffering violence. Special consideration should be given to more vulnerable groups, including women living with disabilities, who are at increased risk of domestic violence and may face further barriers in reaching the services they need, such as social assistance and home care,due to curfews and social distancing or restrictions on movement. COVID-19 has uncovered the existing inequalities in families and society and exacerbated the structural factors that contribute to domestic and intimate partner violence. Displaced and refugee women, and women living in conflict-affected areas are also particularly vulnerable due to high population density, close proximity in living conditions; poor water, sanitation and hygiene; and limited health, social and protection services.
Keywords: Domestic Violence, Pandemic, Corona virus, Household, Uganda